Balões estratosféricos e sua utilização em pesquisas atmosféricas e cósmicas - Malmonge Martin, Inácio (Revista Ceres, 2025)
This study describes the development of a dynamic stratospheric ballonlaunching technique in Brazil. One indirect empirical process to determine the lifting gas force was used to find the gas volume necessary for the ballon to reach a desired height.